Analisis Teologis Dampak Kejatuhan Manusia Dalam Berdasarkan Dari Kejadian 3 - Noh Asbanu; Desriang Zebua; sariyanto sariyanto (REI MAI: Jurnal Ilmu Teologi dan Pendidikan Kristen, 2026)
The fall of Adam and Eve in Genesis 3 is a pivotal event in Christian theology that altered humanity's relationship with God, others, and nature. This study aims to analyze the theological, moral, and existential impacts of the fall and its relevance to contemporary issues such as social conflicts and ecological crises. The research employs a qualitative approach through the analysis of biblical texts, theological literature, and contextual studies. The findings reveal that the original sin stemmed from a lie that sowed doubt about God’s goodness, leading to disobedience. Consequently, humanity’s relationship with God was broken, divisions among people emerged, and harmony with nature was disrupted. In conclusion, the fall underscores the necessity of the doctrine of redemption to restore damaged relationships. The church is expected to play an active role in spiritual education and moral guidance to help address the effects of sin in human life.